Taxonomic notes on the Volucella pellucens species group (Diptera: Syrphidae) with a description of one new species from the Eastern Palaearctic - Choi, Deuk-Soo; Ôhara, Kenji; Han, Ho-Yeon (Zootaxa, 2006)
Volucella thompsoni n.sp. is described and illustrated. The following characters distinguish it from the other species of the Volucella pellucens group: 1) abdominal tergite 2 longer than tergite 3, or at most 2.4x wider than long; 2) male basoflagellomere in lateral view slightly constricted in middle; and 3) surstylus greatly shortened in lateral view. This species was erroneously named as V. matsumurai Han et Choi replacing V. pellucens var. japonica Matsumura for homonymy. Subsequent examination of the holotype of V. pellucens var. japonica revealed that it was merely a variant of V. pellucens tabanoides Motschulsky. In addition, we compared V. thompsoni n.sp. with the other known species and subspecies of the pellucens species group (V. inflata, V. nigricans, V. pellucens pellucens and V. pellucens tabanoides). For V. pellucens, we discussed the status of the Asian and European populations, and provided a justification for recognizing them as two subspecies. We also provided a key and diagnoses for the included species with the detailed illustrations of their male genitalia and other body parts.